PENGEMBANGAN JALUR TREKKING GUNUNG DAPI DAPI UNTUK PENGUATAN ATRAKSI WISATA DI DESA BUDO, KAB. MINAHASA UTARA PROVINSI SULAWESI UTARA - Bet El Silisna Lagarense; Mex U. Pesik (Jurnal Ilmu Pariwisata, 2024)
Budo Village is a Tourism Village in the District. North Minahasa is in the top 50 in the 2022 Indonesian Tourism Village Award event held by the Indonesian Ministry of Tourism and Creative Economy. Budo Village currently relies on the mangrove trail tourist attraction which already receives 200-250 tourist visits per day, both local and international. In developing the main tourist attraction, namely the Mangrove trail, Budo Village, it turns out that it has started to experience overcrowding at one point, so a new tourist attraction is needed as an alternative attraction in Budo Village, namely Trekking of Mount Dapi Dapi which has beautiful natural view. This research focused is aims to design the Mount Dapi-Dapi for Ecotourism trekking trail to attract.